Rockmagnetic Characterization of the Quaternary Fluviolacustrine Sediments of the Thimi Section, Kathmandu Valley, Nepal - Gautam, Pitambar; Neupane, Ghanashyam; Huyghe, Pascale; Rochette, Pierre; Igarashi, Yaeko (Bulletin of the Department of Geology, 2022)
The fine-grained silt/clay sediments sampled at 38 levels of a 21 m thick segment at the Thimi outcrop in the Kathmandu valley have been studied for their rockmagnetic properties. These sediments have yielded consistently normal magnetic polarity and 14C ages determined by various workers between 20 and 45 kyrs or even more. They were measured for a set of rock magnetic parameters: low-field magnetic susceptibility, parameters derived from isothermal remanent magnetization (IRM) acquisition and demagnetisation (IRM0.3T, IRM3T, MDFIRM), anhysteretic remanent magnetization (ARM) (ARMtot, ARM(30 mT)/ARMtot, χARM), hysteresis parameters, etc. Several relationships between these parameters have been suggested for the Kathmandu valley sediments. Four rockmagnetic zones, based on the minor variations in magnetic mineral types and grain size parameters, are proposed and their possible relationship to the published pollen data has been discussed.